PERAN ORANG TUA DAN GURU DALAM MENGATASI PASSIVE LEARNER PADA SISWA KELAS 4 DI MI TERBIYATUL ISLAM - Mudafar, Roy Zaki; Choerul Anwar; Nur Fitri Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of parents and teachers in overcoming passive learner students in grade 4 of MI Tarbiyatul Islam. Passive learners are students who are less active in the learning process and tend to be passive when interacting in class. The method used is descriptive qualitative with data collection techniques in the form of observation and interviews. The results of the study indicate that the role of parents in providing learning support at home and good communication with the school greatly helps increase students' enthusiasm for learning. Meanwhile, teachers play a role through a varied approach and special attention to passive students. Collaboration between parents and teachers has proven effective in increasing students' active participation in class.